Comparative assessment of manual material handling using the two methods of KIM and revised NIOSH lifting equation in workers in small industries in Kabudarahang - Fatemeh ROSTAMI; Mehdi HOJATI (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: Manual handling expose workers force, awkward postures, and repetitive motions. The aim of the present study was the assessment of lifting capacity by the KIM and NIOSH equation methods. Methods: This descriptive-analytical study was conducted in 2018 on 25 workers of small-scale industries in Kabudarahang active in production of flour, sausage and salami, precipitated calcium carbonate and building materials. It was conducted using KIM method and NIOSH equation and then the results were compared by Cohen's kappa coefficient and SPSS software version 18. Results: According to the KIM method, the highest and lowest risk ratings were for material loading and transferring the material, respectively. The results of the NIOSH equation, respectively, assigned the highest and lowest CLI values ​​to bag loading and material transferring activities. The results showed that, in both methods, the loading activity of the materials had high risk due to the high load weight, the number of times of lifting load, the high height difference of the harvest place and placement. Conclusion: The results of evaluation of both methods showed that the risk level was high in 92% of the workers. The results of the two methods showed that both methods agreed on 71% risk estimation. Also, for reasons such as high altitude difference between the source and the destination of the load transporting and the high repetition of the load shift, the probability of musculoskeletal disorders was high in all the stations examined.